PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT BPR NUSANTARA BONA PASOGIT 17 (BANK BPR) - Emanuella Marpaung; Ahmad Rivai; Emma Novirsari (MTU PRESS, 2022)
This study discusses the effect of competence and compensation on the performance of employees of PT. BPR Nusantara Bona Pasogit 17. Employees of PT. BPR Nusantara Bona Pasogit 17 has a total population of 84 people and the sample of this study was taken with a saturated sample technique of 84 people. Data collection in this research is by questionnaire, interview and documentation. Data were analyzed using multiple linear regression analysis models. The results showed a comparison of positive and significant competencies on employee performance > ftabel (6,027 > 3.11) with a significant level (0,000 < 0.01). Partially, positive and significant percentage of job satisfaction, tcount > ttable (2.333 > 1.663) and significant value (0.022 > 0.01). Partially positive and significant communication on employee performance tcount > ttable (3.471 > 1.663) and a significant value of 0.001 < 0.01